Challenges of the 21st Century: Social Media and E-Government. Herausforderungen des 21. Jahrhunderts: Social Media und E-Government. - Fietkiewicz, Kaja Joanna (My University, 2018)
This thesis covered some of the most important and current topics that emerged with the development of the knowledge society. E-government and social media usage in diverse contexts (private, public, or legal), should be continuously investigated to be in the loop with current trends and status quo of user information behaviour. Today, the changes related to technology and the Web are occurring at a very fast pace, therefore, there is need for constant control and adjustment of the surrounding circumstances (e.g., the legal system). Preventive actions are better than damage control. After all, it is in our hands how the future societies, cities, and world will look like. The shift from the traditional red-tape to efficient, digital public services is still in progress and, therefore, requires constant investigation. Then, the focus of the investigation is redirected onto social media usage in different contexts. Social media also became typical tools applied by the knowledge society. Different areas investigated in this study address aspects of contemporary importance, from general social media users' characteristics, through online journalism and news dissemination on Twitter, usage of new live streaming services, also including problematic usage (law infringements), up to social media marketing and crowdfunding or competition (law) on social media markets. In view of the increased popularity of e-government as an important aspect of the development of knowledge society, the beginning of this information science research focuses on three questions. First one concerns the overall state of e-government, or its "maturity," in selected 31 Informational Cities. This also required the development of a suitable method to measure the maturity of an e-government website. Furthermore, to properly serve the citizens, e-government needs to be understandable and usable. Therefore, the second research question concerns the usability of e-government in Informational Cities. Finally, e-government portals are supposed to serve many different stakeholders. Due to its (potential) suitability to be understood and used by all the different user groups, it can be seen as a so-called boundary object. The final research question addresses this subject in more detail, that is, "How do e-government websites handle boundary documents?"
Keywords: Verwaltung; E-Government; Information; Informationstechnologie; Medien; Öffentlichkeit; Rechtslage; Datenschutz; Wissensgesellschaft; Internet; Social Media; Lebensalter; Nutzungsverhalten; Internationaler Vergleich; Empirische Untersuchung; Informationsfreiheit